2004
DOI: 10.1007/s00213-004-1941-4
|View full text |Cite
|
Sign up to set email alerts
|

The CB receptor agonist WIN 55,212-2 fails to elicit disruption of prepulse inhibition of the startle in Sprague-Dawley rats

Abstract: These findings suggest WIN does not impair sensorimotor gating in Sprague-Dawley rats and confirm clinical evidence according to which cannabis is an unlikely causative of psychosis among non-vulnerable individuals. Nonetheless, since in other studies the same compound was shown to induce PPI alterations in Wistar rats, our results are also suggestive that genetic differences might be critical for the development of cannabis-induced cognitive disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 70 publications
(70 reference statements)
5
22
0
Order By: Relevance
“…These results can explain the findings reported in the literature that cannabinoid agonists increase (Stanley-Cary et al 2002), decrease (Nagai et al 2006;Schneider and Koch 2002), or have no effect (Bortolato et al 2005;Bortolato et al 2006a;Bortolato et al 2006b;Mansbach et al 1996;Martin et al 2003) on PPI. Furthermore, corticosteroid effects of cannabinoid agonists on PPI elucidated here may be the mechanism by which chronic cannabinoid treatment in pubertal rats produces changes in adult PPI (Schneider and Koch 2003), since chronic corticosterone treatment has been shown to similarly impair PPI (Ingram et al 2005;Stevens et al 2001).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These results can explain the findings reported in the literature that cannabinoid agonists increase (Stanley-Cary et al 2002), decrease (Nagai et al 2006;Schneider and Koch 2002), or have no effect (Bortolato et al 2005;Bortolato et al 2006a;Bortolato et al 2006b;Mansbach et al 1996;Martin et al 2003) on PPI. Furthermore, corticosteroid effects of cannabinoid agonists on PPI elucidated here may be the mechanism by which chronic cannabinoid treatment in pubertal rats produces changes in adult PPI (Schneider and Koch 2003), since chronic corticosterone treatment has been shown to similarly impair PPI (Ingram et al 2005;Stevens et al 2001).…”
Section: Discussionsupporting
confidence: 80%
“…PPI is decreased in rats by drugs that induce psychosis in people, such as amphetamine (Curzon and Decker 1998;Mansbach et al 1988) or phencyclidine (PCP) (Curzon and Decker 1998), although the effects of these compounds or cannabinoids on PPI in humans are inconsistent (Kedzior and Martin-Iverson 2006;Quednow et al 2004;Swerdlow et al 2002;Swerdlow et al 2003). PPI effects of cannabinoids in rats are also unclear with no effects (Bortolato et al 2005;Bortolato et al 2006a;Bortolato et al 2006b;Mansbach et al 1996;Martin et al 2003), increases (Stanley-Cary et al 2002) and decreases (Nagai et al 2006;Schneider and Koch 2002) being reported.…”
Section: Introductionmentioning
confidence: 99%
“…Since WINinduced PPI deficits have not been found in one other study (Bortolato et al 2005) using Sprague-Dawley rats, with a different test system and procedure, we strived to replicate our initial finding in Wistar rats. WIN leads to markedly decreased PPI at all pre-pulse intensities, thus reproducing previous results obtained in our laboratory (Schneider and Koch 2002).…”
Section: Discussionmentioning
confidence: 96%
“…The startle reflex was assessed as described by Bortolato et al (2005). At 45 min after treatment with either AM404 or vehicle, rats were placed in a startle reflex apparatus (Med Associates, St Albans, USA) for a 5 min acclimatization period with a 70 dB background noise, which continued for the remainder of the session.…”
Section: Startle and Ppi Of Startlementioning
confidence: 99%